2017
DOI: 10.21276/apalm.1468
|View full text |Cite
|
Sign up to set email alerts
|

RBC Histogram as supplementary diagnostic tool with peripheral smear examination in evaluating anemias

Abstract: Background: Red blood cell(RBC) histogram provide an idea about morphological changes of red blood cells in hematological disorders. Peripheral smear examination findings are usually correlated with complete blood cell counts by automated analyzer. To known the utility and advantage of red cell histogram and correlation of microscopic examination of peripheral smear with automated histogram pattern.Methods: Blood sample was collected from 220 anemia patients in ethylene diamine tetra acetic acid (EDTA) tubes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 4 publications
5
8
0
Order By: Relevance
“…In present study of 1500 cases, maximum numbers of cases are having Microcytic anemia (70%) followed by normocytic (18%), Dimorphic (8%) and Macrocytic (4%). Other studies like sandhya et al [5] Chavda J et al [6] & Byna Syam Sundara Rao et al [8] were also found similar findings regarding distribution of anemia cases. Our study of RBC histogram showed normal curve (18%), left shift (29%), right shift (6%) Broad base (40%), short peak (2%) and bimodal (5%) and these findings regarding to RBC histogram were also correlated with other studies like sandhya et al [5] Chavda J et al [6] & Rao BSS et al [8] (Table no.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In present study of 1500 cases, maximum numbers of cases are having Microcytic anemia (70%) followed by normocytic (18%), Dimorphic (8%) and Macrocytic (4%). Other studies like sandhya et al [5] Chavda J et al [6] & Byna Syam Sundara Rao et al [8] were also found similar findings regarding distribution of anemia cases. Our study of RBC histogram showed normal curve (18%), left shift (29%), right shift (6%) Broad base (40%), short peak (2%) and bimodal (5%) and these findings regarding to RBC histogram were also correlated with other studies like sandhya et al [5] Chavda J et al [6] & Rao BSS et al [8] (Table no.…”
Section: Discussionsupporting
confidence: 68%
“…Shift in one direction or another can be of diagnostic importance and in association with other CBC parameters such as RBC distribution width (RDW) and RBC indices (MCV, MCH, MCHC) it has been found abnormal in various hematological conditions [2][3][4] . A lot of studies [5][6][7][8][9] have been done to assess the efficacy and significance of red blood cell parameters in different hematological conditions. We undertake this study to study RBC's histograms in various anemias and to compare our findings with available literature.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the most affected age group was 20-30 years followed by 30-40 years which was comparable to the results of similar studies done by Korgaonker and Shashidhar 8 Kumar et al, 9 Cook et al 10 Our study of RBC histogram showed normal curve (7%), left shift (27%), right shift (14%), broad base (38%), and bimodal (14%) and these findings regarding to RBC histogram were also correlated with other studies such as Sandhya and Muhasin, 11 Chavda et al, 2 Rao et al, 12 and Shrivastav et al 13 The most common type of anemia observed in our study was dimorphic anemia (combined nutritional deficiency) followed by microcytic hypochromic anemia indicative that the most common anemia observed in Vindhya region population is combined nutritional deficiency which is in contrast with studies by Sandhya and Muhasin, 11 Chavda et al; 2 and Rao et al, 12 which shows microcytic hypochromic anemia as the most common distribution pattern.…”
Section: Agesupporting
confidence: 91%
“…The rBC count does not affect by WBCs count is increased by beyond 50000 cells / cumm. [10][11][12][13] In the present study of 500 cases, the maximum number of instances are having Microcytic anemia followed by normocytic, Dimorphic and Macrocytic. Other studies like sandhya al 14 , BynaSyamSundara rao et al 15 , Chavda J et al 16 were also found similar findings of anemia cases regarding Distribution.…”
Section: Discussionmentioning
confidence: 97%